Implementation of Integrated Curriculum in Islamic Education in Elementary Madrasah: Case Study of MI Al Ma'arif Merauke - Alqasdijal, Amran; Hakim, Abd; Junaenah; Mustamin (Al-Ulum, 2025)
This study examines the implementation of an integrated curriculum in Islamic Education at Al Ma'arif Elementary School in Merauke Regency. The problem addressed is how Islamic values ​​are integrated into the curriculum, as well as the challenges and supporting factors in its implementation. The purpose of this study is to describe the implementation of the integrated curriculum at the school and analyze the factors that support and hinder its implementation. The method used is a qualitative approach with a case study design, involving interviews, observations, and documentation studies to collect data from the principal, vice principal of curriculum, teachers, and students. The results show that curriculum integration is carried out by linking subject matter with Islamic values, such as connecting science with the greatness of Allah SWT. The learning approach used involves discussion and practice, and teachers are expected to be role models in implementing Islamic values. However, there are several inhibiting factors, such as limited time, facilities, variations in student abilities, and limited teacher understanding of the integrated curriculum. The main supporting factors are the commitment of the principal and parental involvement in supporting religious education. This study implies that although the implementation of an integrated curriculum can strengthen students' religious understanding, challenges related to resources and differences in student abilities need to be addressed to achieve more effective implementation.